2003
DOI: 10.1002/cne.10915
|View full text |Cite
|
Sign up to set email alerts
|

Expression of constitutively active p21H‐rasval12 in postmitotic pyramidal neurons results in increased dendritic size and complexity

Abstract: The small G protein p21Ras is a critical molecular switch for relaying neurotrophic actions and is essential for normal functioning and plasticity of the nervous system. In this study, the morphogenetic effects of p21Ras were investigated on neurons in vivo. Morphological changes of layers II/III and Vb commissural pyramidal neurons of the primary somatosensory cortex were analyzed in transgenic mice expressing permanently active p21H-RasVal12 in postmitotic neurons. Pyramidal cells were retrogradely labelled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
1

Year Published

2003
2003
2010
2010

Publication Types

Select...
6
1

Relationship

6
1

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 75 publications
5
37
1
Order By: Relevance
“…In a previous study, a striking increase of dendritic tree size was verified in the pyramidal neurons of synRas mice neocortex [4]. Surface area and volume of proximal and intermediate dendritic segments were significantly augmented which was caused mainly by increased dendritic diameter, and not by segment elongation.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…In a previous study, a striking increase of dendritic tree size was verified in the pyramidal neurons of synRas mice neocortex [4]. Surface area and volume of proximal and intermediate dendritic segments were significantly augmented which was caused mainly by increased dendritic diameter, and not by segment elongation.…”
Section: Discussionmentioning
confidence: 70%
“…The volume of the neocortex of synRas mice is expanded up to 25% as compared to wildtype mice. In particular cortical pyramidal neurons express the synRas construct at high levels resulting in a dramatically enlarged volume of the cortical pyramidal cells which is mainly caused by increased dendritic diameter and tree degree [4,5]. The number of neurons, however, remains unchanged [3].…”
Section: Introductionmentioning
confidence: 99%
“…In Ref. [2], we found that the volume of the neocortex of synRas mice is expanded up to 25% as compared to wildtype mice. This is due to the dramatically enlarged volume of the cortical pyramidal cells caused mainly by increased dendritic diameter and tree degree, whereas the number of neurons remains unchanged.…”
Section: Resultsmentioning
confidence: 91%
“…The details of experimental procedures have been described in [2]. The main deliverables were two sets of retrogradely labelled pyramidal cells (28 cells from wildtype and 28 cells from transgenic mice) which were reconstructed ( Fig.…”
Section: Experimental Basis and Reconstructionsmentioning
confidence: 99%
See 1 more Smart Citation